The Borrowings Kṣuta-/kṣut- (“Inimical”) and Vidumāla- (“Retrograde”) in Sanskrit Astrological Texts and the Representation of Semitic ʿayn in Similar Loans - Wikander, Ola (History of Science in South Asia, 2022)
This short article deals with the etymologies of two Perso-Arabic loans that function as technical terms in Tājika (Indian astrology imported from the Perso-Arabic cultural area), both appearing in the works of the 13th century CE astrological author Samarasiṃha. The terms are kṣuta-/kṣut- (“Inimical”) and vidumāla- (“Retrograde”) - the meanings of both have been clear for some time, but the article elucidates their exact etymologies, and uses them to argue a rather complex mode of scientific/scholarly transmission, possibly involving as many as four languages: Arabic, Persian, Old Gujarati (or other northern Indo-Aryan vernaculars of the time), and finally Sanskrit. Finally, the article discusses the renderings of the voiced pharyngeal fricative in loans of this type in the light of early Modern Persian orthography and phonology.